SOLUTION
We want to find which of the following is a solution to
![2x-y=-1](https://img.qammunity.org/2023/formulas/mathematics/college/lne4ywvxelfje5k9sddbqfajubdussdqk6.png)
Let's try the first option (2, -1)
So, the first value will be x, so if we get y as 1, then this option is correct
Now replacing x for 2 in the equation, we have
![\begin{gathered} 2x-y=-1 \\ 2(2)-y=-1 \\ 4-y=-1 \\ y=4+1 \\ y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y1v888kvm4on164sza5czdpocx9ipu2bew.png)
So, this is not correct. Let us try the next option (1, 2)
Let's put x to be 1 and see what y becomes
![\begin{gathered} 2x-y=-1 \\ 2(1)-y=-1 \\ 2-y=-1 \\ y=2+1 \\ y=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mw01ho822ym39v6s54jdapttj6js0t0leg.png)
So, when x = 1, y =3, If you look at the 4th option, we can see (1, 3), which means x = 1 and y = 3, hence
the correct answer is (1, 3) the 4th option